Twin iterative solutions for a fractional differential turbulent flow model - Wu, J.; Zhang, Xinguang; Liu, Lishan; Wu, Yong Hong (SpringerOpen, 2016)
We investigate the existence of twin iterative solutions for a fractional p-Laplacian equation with nonlocal boundary conditions. Using the monotone iterative technique, we establish a new existence result on the maximal and minimal solutions under suitable nonlinear growth conditions. We also consider some interesting particular cases and give an example to illustrate our main results.